“Treat Them with the Reverence of Archivists”: Records Work, Grief Work, and Relationship Work in the Archives - Douglas, Jennifer; Alisauskas, Alexandra; Mordell, Devon (Archivaria, 2019)
In this article, we take up Geoff Wexler and Linda Long’s call to explore the ways in which records and recordkeeping are “bound up” in experiences of loss and grieving. Drawing on theoretical and clinical literature on bereavement, we introduce the concept of grief work and investigate some ways in which grief work can be performed through the creation, use, organization, and preservation of records. We illustrate our study of records work as grief work with examples from the Hamilton Family Fonds at the University of Manitoba Archives and Special Collections, the Sylvia Plath collections at Smith College and Indiana University, and the Lara Gilbert Fonds at the University of Victoria Archives. Finally, we suggest some impacts – especially the ethical impacts – a grief work perspective might have on the ongoing development of archival theory and methodology. This article lays the conceptual groundwork for a larger, ongoing study on recordkeeping, grief work, and the concept of archival care. RÉSUMÉ Dans cet article, nous répondons à l’appel lancé par Geoff Wexler et Linda Long à explorer comment les documents et la gestion des documents sont imprégnées des expériences de perte et de deuil. Puisant dans les études théoriques et cliniques sur le deuil, nous présentons le concept de travail de deuil et explorons des façons par lesquelles le travail de deuil peut s’effectuer par la création, l’utilisation, l’organisation et la préservation de documents. Des exemples du fonds Hamilton Family aux University of Manitoba Archives and Special Collections, des collections Sylvia Plath au Smith College et à l’Indiana University et du fonds Lara Gilbert aux University of Victoria Archives servent à illustrer notre étude du travail avec les documents comme travail de deuil. Enfin, nous évoquons certaines retombées, particulièrement au niveau éthique, qu’une perspective du travail de deuil pourrait avoir sur le développement de la théorie et de la méthodologie archivistiques. Cet article pose les bases conceptuelles de l’étude plus large et continue de la gestion des documents, du travail de deuil et de la notion de traitement archivistique.